Rancang Bangun Sistem Informasi Pencatatan Keuangan dan Penjualan Berbasis Progressive Web App (PWA) pada Kantin Dinda Gedung Ventura - Muhamad Marseal Purwo Syah Putra; Afiani Agus Abdillah; Muhammad Aziz Saputra; Ananda Juliana Jaludin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
This study aims to design and build a financial and sales recording information system at Kantin Dinda in the Ventura Building based on a Progressive Web App (PWA). Kantin Dinda has been facing constraints in manual transaction data processing for both cash and QRIS payments, which triggers the risk of data loss, unstructured recording, and delays in presenting daily, weekly, and monthly income summaries. The research methods applied include field observations, interviews, and system development using the Agile Scrum approach. The result of this research is the "Kantin Dinda Ledger" application based on PWA, which is capable of integrating transaction data automatically, simplifying financial reporting, and increasing the operational efficiency of the canteen so that managers can monitor business performance accurately and structured.